POTENTIAL OF DIETARY FIBER AND ANTIOXIDANTS FROM COFFEE SKIN AS A FOOD PRODUCT IN PREVENTING OBESITY: SYSTEMATIC REVIEW - Eleora Setiawan, Sia, Clarissa; Yuliantara, Arri; Rizkaprilisa, Windy; Paramastuti, Ratih; Hapsari, Martina Widhi (Science Technology and Management Journal, 2024)
Obesity is a global health problem that continues to increase and is a major concern in efforts to maintain public health. In this context, the role of food in preventing obesity becomes very important. Food components that have an impact on preventing obesity, namely dietary fiber and antioxidants. Coffee skins are often not utilized, even though they contain high amounts of dietary fiber and antioxidants which can help prevent obesity. The purpose of this article is to explain the potential of dietary fiber and coffee skin antioxidants to prevent obesity. The method used to complete this article is by using the literature study method. Coffee skin consists of several parts, namely pulp, parchment, and silverskin. The coffee skin is obtained from processing coffee berries or coffee cherries which go through wet, dry and semi-wet processing stages. Food products made with coffee skins contain high levels of dietary fiber and antioxidants so they can prevent obesity. Food products made using coffee husks include tea, biscuits, granola, syrup, chocolate and kombucha. Utilizing coffee skins as a food ingredient created food product that are not only delicious but also healthy because they can help individuals maintain a balanced body weight. The dietary fiber and antioxidants contained in coffee skin have the potential to prevent obesity so they can be used as food products.